The State of Studying the Evolution of the Ukrainian Schooling of Western Diaspora in Pedagogical Science - Rybak, Tetiana (Pedagogical Discourse, 2017)
Іn the article, the author analyzes the historical and graphic components of the study of the evolution of the Ukrainian schooling of the Western Diaspora in pedagogical science, explicitly reveals the objective and subjective tendencies in the development of textbooks on provision of educational material for primary, secondary and tertiary school students in Western countries, where Ukrainians were from. It is proved that the Ukrainian emigration school in the second half of the twentieth century passed the evolutionary path that other nations had overcome in a foreign-language environment. The activity of the Ukrainian Studies School outside the Motherland is a unique example of preserving national identity in the history of pedagogy, forcing the younger generation of knowledge about Ukraine, its customs and traditions. Practice convinces that children who have learned the basics of science in the Ukrainian language and literature in a foreign-language environment at an early age, fluent in their mother tongue throughout their lives. It was found out in the process of studying and analyzing the problems that many scientific and popular scientific achievements in Ukrainian historiography are devoted to the study of the activities of Ukrainian educational institutions abroad. It is observed that researchers focus on basic pedagogical principles summarizing historiography on this theme, especially the teaching of the Ukrainian language and literature. Therefore, an array of primary sources, scholars’ works on Ukrainian emigration schools is divided into four groups. Scientific achievements of literary and linguistic-emigrants influenced the content of Ukrainian philology. Thus, methodologists and practicing teachers in the countries of the Western world made a significant contribution to the development of pedagogy, methodology of Ukrainian literature and the development of textbooks on the literature: works on the theory of methodology of literature - K.Kysylevskyi, L.Kysylevska-Tkach, B.Skandriy, P.Bohatskyi, A.Yuryniak, D.Nytchenko, P. Bohatskyi, etc. Readers, textbooks and textbooks for the elementary and secondary school of such well-known linguists as: K.Kysylevskyi, L. Biletskyi, M.Deyko, P.Volyniak, I.Dodnaruk, V.Radzykevych, M.Ovcharenko, D.Nytchenko, E. Fedorenkl, O.Kopach, etc. are widely used in the western world. There are works in the article, where the actual history of emigration schooling is widely present in Ukrainian historiography on the study of the activities of Ukrainian educational institutions abroad.